The BERAKSI Learning Model: Optimizing the Holistic Development of Early Childhood - Nongko, Pahenra A.; Bundu, Patta; Rauf, Bahkrani A. (Universitas Sebelas Maret, 2025)
Early Childhood Education has a vital role in the holistic development of children, including cognitive, social, emotional, and motoric aspects. However, traditional learning approaches are often less effective in accommodating these developmental needs. To overcome this problem, the BERAKSI (Playing, Creating, Discussing, and Cheerful) Learning Model was developed as an innovation that aims to increase involvement and optimal development of young children. This research will discuss the implementation of the BERAKSI Learning Model, which can optimize the development of early childhood in cognitive, social, emotional, and motoric aspects. The aim is to develop and implement the BERAKSI Learning Model to optimize the holistic development of early childhood. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews, and document analysis in several early childhood schools. Data analysis was carried out thematically to identify patterns and effects from applying this model. The research results show that the BERAKSI Learning Model is successful in increasing children's involvement in the learning process, improving cognitive, social, and emotional abilities, and creating a pleasant learning atmosphere. Teachers who have been trained are able to implement this model well, and the curriculum developed supports the success of the BERAKSI model. The implications of this research indicate that the BERAKSI approach can be adopted more widely in early childhood education in Indonesia. The proposed solutions include teacher training, development of appropriate curricula, and provision of supporting facilities and resources, as well as ongoing evaluation to adjust learning strategies. With these steps, the BERAKSI Learning Model is expected to have a significant positive impact on the holistic development of early childhood.